214k views
5 votes
3x-6y=12 solve the equation for y. drag and drop to order the steps​

User Warblr
by
6.0k points

1 Answer

2 votes

For this case we have the following equation:


3x-6y = 12

We must solve the equation for the variable "y":

Subtracting 3x from both sides of the equation we have:


-6y = 12-3x

Dividing by 6 to both sides of the equation:


-y = \frac {12} {6} - \frac {3x} {6}\\-y = 2- \frac {x} {2}

We multiply by -1 on both sides of the equation:


y = \frac {x} {2} -2

Answer:


y = \frac {x} {2} -2

User Ebottard
by
5.6k points